Review of Research on the Rare-Earth Doped Piezoelectric Materials - Chen, Yan; Zhang, Donglai; Peng, Zhong; Yuan, Maodan; Ji, Xuanrong (Frontiers in Materials, 2021)
The piezoelectric materials, such as ceramics, crystals and films, have widely applications in mechanical industry, medical imaging, electronic information and ultrasonic devices, etc. Generally, adding oxide dopants, or introduction of new solid solutions to form the morphotropic phase boundary of the piezoelectric materials were the general strategies that can enhance the electric properties. At present, rare-earth doping piezoelectric materials have been attracted much attention due to the multifunctional performance of combining with piezoelectric and photoluminescence properties into a single entity, which has potential applications in optoelectronic fields. An overview of the recent investigations and perspectives on rare-earth doped piezoelectric ceramics, single crystals and films were presented.